Recent Update on UV Disinfection to Fulfill the Disinfection Credit Value for Enteric Viruses in Water - Augsburger, Nicolas; Rachmadi, Andri Taruna; Zaouri, Noor; Lee, Yunho; Hong, Pei-Ying (Environmental science & technology, 2021)
Ultraviolet (UV) radiation alone or in combination with other oxidation processes is increasingly being considered for water disinfection because of stringent regulatory requirements for pathogen inactivation. To fulfill this requirement, an appropriate UV dose or fluence (mJ/cm ) is applied to combat enteric viruses in surface or treated water. There is a need for a cumulative review on the effectiveness of current and emerging UV technologies against various types of human enteric viruses. We extracted the kinetics data from 52 selected experimental studies on enteric virus inactivation using low pressure (LP-UV), medium pressure (MP-UV), UV-LED, and advanced oxidation processes (AOPs) and applied a simple linear regression analysis to calculate the range of UV fluence (mJ/cm ) needed for 4-log inactivation. The inactivation of adenoviruses with LP-UV, MP-UV, and UV/H O (10 mg/L) required the highest fluence, which ranged from 159 to 337, 45, and 115 mJ/cm , respectively. By contrast, when using LP-UV, the inactivation of other enteric viruses, such as the Caliciviridae and Picornaviridae family and rotavirus, required fluence that ranged from 19 to 69, 18 to 43, and 38 mJ/cm , respectively. ssRNA viruses exhibit higher sensitivity to UV radiation than dsRNA and DNA viruses. In general, as an upgrade to LP-UV, MP-UV is a more promising strategy for eliminating enteric viruses compared to AOP involving LP-UV with added H O or TiO . The UV-LED technology showed potential because a lower UV fluence (at 260 and/or 280 nm wavelength) was required for 4-log inactivation compared to that of LP-UV for most strains examined in this critical review. However, more studies evaluating the inactivation of enteric viruses by means of UV-LEDs and UV-AOP are needed to ascertain these observations.